2020
DOI: 10.1038/s41587-020-0742-6
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive library of human transcription factors for cell fate engineering

Abstract: Human pluripotent stem cells (hPSCs) offer an unprecedented opportunity to model diverse cell types and tissues. To enable systematic exploration of the programming landscape mediated by transcription factors (TFs), we present the Human TFome, a comprehensive library containing 1,564 TF genes and 1,732 TF splice-isoforms. By screening the library in three hPSC lines, we discovered 290 TFs, including 241 previously unreported, that induce differentiation in four days without alteration of external soluble or bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
121
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(137 citation statements)
references
References 90 publications
2
121
0
Order By: Relevance
“…These tools could identify iPSC or early-stage markers that define suitability for an efficient SC-islet differentiation 65 or genes to overexpress in iPSCs to initiate or improve differentiation. 91 In addition, reporters to enable robust readouts of function and maturation after cell fate specification would help both cell therapy development and drug screening applications. 92 , 93 , 94 Ideally, SC-islets would be indistinguishable from primary islets for transplantation, specifically in terms of glucose-stimulated insulin secretion, but further protocol improvements are needed to achieve this.…”
Section: Future Outlookmentioning
confidence: 99%
“…These tools could identify iPSC or early-stage markers that define suitability for an efficient SC-islet differentiation 65 or genes to overexpress in iPSCs to initiate or improve differentiation. 91 In addition, reporters to enable robust readouts of function and maturation after cell fate specification would help both cell therapy development and drug screening applications. 92 , 93 , 94 Ideally, SC-islets would be indistinguishable from primary islets for transplantation, specifically in terms of glucose-stimulated insulin secretion, but further protocol improvements are needed to achieve this.…”
Section: Future Outlookmentioning
confidence: 99%
“…Differentiation of OPCs and subsequently OLs from hiPSCs or hESCs can be achieved by recapitulating the signaling processes associated with differentiation (Goldman and Kuypers, 2015 ), either pharmacologically by timely addition of agonist and antagonists during the differentiation process (Douvaras and Fossati, 2015 ), or by driving expression of key regulatory genes, such as SOX10 and OLIG2 in ESCs (Pawlowski et al, 2017 ), or SOX10, OLIG2 and NKX6.2 (Ehrlich et al, 2017 ) and SOX9 in hiPSCs (Ng et al, 2020 ). A combination of both pharmacological and genetic differentiation methodologies can also be used to great synergistic effect (García-León et al, 2020 ).…”
Section: Culture Systemsmentioning
confidence: 99%
“…As mentioned, these protocols enable the production of relatively large amounts of OPCs and OLs, which can be used therapeutically (Egawa et al, 2016 ; Morales Pantoja et al, 2020 ) or for experimentation. Xenograft experiments have shown that hiPSC-derived OPCs/OLs survive and can influence disease processes in model animals (Wang et al, 2013 b; Kawabata et al, 2016 ; Feng et al, 2020 ; Ng et al, 2020 ). Finally, and perhaps most illuminating are studies where patient-derived iPSCs are used to make OPCs/OLs, which are then used to study disease processes (for review: Chanoumidou et al, 2020 ).…”
Section: Culture Systemsmentioning
confidence: 99%
“…II. Implantation for a specific period of time of biodegradable nanobiosensors -nanites -nanomachines -molecular machines for therapeutic issues [3] We can also send [with automation or with technological mandates via ultrasound pulses (ultrasound scan will monitor the nanites -nanomachines -molecular machines for when will arrive to the targets in order to hook up there via activation)] each time when it is a must for health issues, safe biodegradable nanitesnanomachines -molecular machines (from safe biomaterials for organisms without metals in order to there is not a problem with MRI & etc scans) which will release safe therapeutic biochemical -medical substances to the correct -desirable cells [safe biodegradable nanites -nanomachines -molecular machines will invade & bind to the correct -desirable cells because of the analogical specific substances that will have for each occasion to their exterior artificial or/and biochemical membrane (like the membrane of cells) or/and they will invade & bind to the correct -desirable cells through their detectable nanobiosensors] & which will monitor the cause of disease & it's development & later will monitor the actions & interactions of safe therapeutic biochemical -medical substances within the cells before be dissolved (for the understanding of which is the safest way to eliminate each disease through safe therapeutic medical substances) for the confrontation of all type of diseases.…”
Section: Main Subjectmentioning
confidence: 99%